“Under Pressure!”: Digital Work, Mental Strain, and Work Performance - Klumpp, Matthias; Ruiner, Caroline; Hagemann, Vera; Meinecke, Jonathan; Debbing, Christina Elisabeth; Hesenius, Marc (International journal of technology and human interaction, 2024)
The use of digital technologies or applications can have positive and negative effects on workers: Digital technologies might support workers' decision-making by providing necessary information, but digital technologies might also lead to time pressure and mental strain. In this paper, the authors specifically analyze the characteristics of digital work and the link to mental strain to estimate the effects on work performance in industry. They report survey data from four German companies in the manufacturing, service, and logistics sector with N=279 participants. Results indicate that technology-based organizational and personal resources mitigate, while technology-based demands enhance mental stress and strain. Time pressure is the most important individual factor increasing mental stress and strain. Mental strain, in turn, negatively influences work performance. Considering such connections is crucial for human resource management in digital work contexts and specifically workers' use of and interaction with technologies beyond the analyzed specific manufacturing, service, and logistics industries.